A rational definition for functional foods: A perspective - Temple, Norman J. (Frontiers in Nutrition, 2022)
Many foods are described as “functional foods”. However, the term is poorly defined. A commonly used definition is that they contain substances or have positive effects on health “beyond basic nutrition.” However, there are several problems with this definition. In many cases healthy foods are included under the term functional foods. A new definition is proposed as follows. Functional foods are novel foods that have been formulated so that they contain substances or live microorganisms that have possible health-enhancing or disease-preventing value, and at a concentration that is sufficiently high to achieve the intended benefit. The added ingredients may include nutrients, dietary fiber, phytochemicals, other substances, or probiotics.